Development and validation of the interactive health literacy scale for college students majoring in kinesiology - Wen, Miaomiao; Wang, Xiaorui; Yin, Zhihua (Frontiers in Psychology, 2026)
IntroductionInteractive health literacy is crucial for sports major college students. However, previous studies have focused on qualitative research, resulting in a lack of quantitative research and a lack of samples from Eastern countries. This study aimed to develop and validate the Interactive Health Literacy Scale for College Students Majoring in Kinesiology (IHLS-CSMK).MethodsA questionnaire was created based on the 60 items of the structural model described in our previous research. Using a questionnaire survey, quantitative data was collected from a sample of 964 sports major college students. We used SPSS 27.0 and AMOS 24.0 to analyze the data and conducted project analysis, exploratory factor analysis, and confirmatory factor analysis to test the data. The IHLS-CSMK consists of 28 concepts, namely mastering health information, promoting health interaction, and solving health problems. The results indicate that IHLS-CSMK has good content validity, internal construct validity, and internal consistency.Results and discussionChinese college students majoring in kinesiology have similarities and differences in interactive health literacy compared to students from other nations. Suggestions to improve the interactive health literacy of college students majoring in kinesiology include: (1) optimizing health education courses and training; (2) enhancing digital and technological support; (3) strengthening diversified health literacy assessment and feedback; and (4) supporting campus environments. The IHLS-CSMK has achieved significant results in China; however, due to differences in cultural backgrounds, health concepts, and education systems, further validation is needed to determine whether this scale is applicable to other countries.